Pediatric COVID-19 Associated Rhabdomyolysis - Parisa Armanpoor; Parvaneh Armanpoor (Journal of Pediatric Research, 2021)

(untitled)
The incidence of rhabdomyolysis secondary to various causes has been reported, especially for viral infections such as influenzas. It is well established that Coronavirus disease-2019 (COVID-19) can include a large array of symptoms during the disease course, but there have been few reports of COVID-19-related rhabdomyolysis. We report a 10-year-old boy who presented with fever, some dry cough, myalgias, and painful walking. His COVID-19 polymerase chain reaction test performed through the nasopharyngeal swab was positive. His first creatinine kinase level was 8,000 U/L. He was treated with isotonic intravenous fluids because of rhabdomyolysis. Muscle weakness and pain are common symptoms of the 2019 novel COVID, but physicians should be aware of the possibility of rhabdomyolysis, especially when patients complain of local pain and weakness in their muscles. Pediatric clinicians should be aware of this complication related to the novel 2019 coronavirus. Timely diagnosis and proper treatment improve the patient’s prognosis.